Learning In Hybrid-Project Systems: The Effects of Project Performance on Repeated Collaboration - Schwab, Andreas; Miner, Anne S. (Academy of Management Journal, 2008)
This study advances contingency theories of performance-outcome learning in hybrid-project systems, in which both project participants and superordinate organizations influence the formation of project ventures. We propose that performance-outcome learning depends on the perceived relevance of prior performance and on organizational control over project participants. We examine this framework using data on 239 U.S. movie projects from the years 1931-40. In keeping with our theory, higher project performance led to future collaborations with the same partners, contingent on prior collaborations, project similarity, and organizational control. Our findings imply distinct patterns of network evolution and unfolding adaptation of hybrid-project systems through slow-moving, local adjustments.